Pengaruh Jam Kerja, Pengalaman Kerja dan Pendidikan Terhadap Pendapatan Karyawan Pada Industri Bordir di Kota Denpasar - Nugraha, Nyoman Tri Arya; Marhaeni, A. A. I. N. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 2, Desember 2012, 2012)
In a study entitled "The Effect of Hours of Work, Work experience, Industry and Education Against Revenue Embroidery in Denpasar." Has a purpose: First, to determine whether hours of work, work experience, and education simultaneously affects the earnings of employees in the embroidery industry in Denpasar. Second, to determine whether hours of work, work experience, and the partial effect of education on earnings of employees in the embroidery industry in Denpasar. This study uses primary data by conducting in-depth interviews and observations to the embroidery industry employees in Denpasar. Hypothesis testing using analytical tools, namely multiple linear regression analysis, F-test, T-test and was preceded by the classic assumption test. The results showed that simultaneous variable working hours, work experience, and education have a significant effect on the earnings of employees embroidery industry in Denpasar and variable working hours, work experience, and the partial effect of education on earnings of employees in the embroidery industry in Denpasar. Based on the data obtained from the processing of Standardized Coefficients, variable work experience has a dominant influence over the other independent variables of 0.363.
Keywords: hours of work; education; income